Axial compressive behavior of new HFC-filled CTS composite walls sheathed with straw-fiber boards. (December 2020) - Xu, Zhifeng; Zhang, Jing; Chen, Zhongfan; Yang, Suhang; Li, Jie
Abstract: In this paper, an innovative high-strength foamed concrete (HFC)-filled cold-formed thin-walled steel (CTS) composite wall sheathed with straw-fiber boards (HFCS composite wall) was proposed. Six full-scale specimens of HFC-filled and unfilled CTS composite walls were tested under compression loading. The influence of HFC strength, stud cross-sectional area, wall thickness and sheathing as main parameters on axial compressive behavior of HFC-filled composite wall were analyzed. Test results indicated that using of HFC changed the failure mode of CTS frame from straw's shear failure to stud's local failure, and improved the wall's axial resistance capacity due to the restrictive effect of HFC on CTS-frame. Moreover, increasing HFC compressive strength further enhanced the bearing capacity of the HFCS composite wall, with little effect on its failure mode. Increasing CTS section area and wall thickness effectively avoided early the stud's local buckling, thereby improved the wall's compressive capacity. However, numerical analysis results showed that the most contribution of the wall components to axial compressive capacity of the HFCS composite wall is CTS studs (52.1%), followed by HFC (42.3%) and straw boards (5.6%), whereas straw board has no obvious effect. Finally, a practical formula for predicting the wall's axial resistance capacity was built by superposition method. The calculated results exhibited better agreement with test and numerical results.